Whistleblowing in a Bureaucratic-Heavy Organization Does it work? - Ach Maulidi (The Indonesian Accounting Review, 2026)
This study explores how employees in bureaucratic organizations interpret the possibility of speaking up about fraud risks. Drawing on institutional theory, this study examines how institutional signals, bureaucratic procedures, and everyday administrative practices shape employees’ interpretations of irregularities and reporting behavior. We used a qualitative approach with semi-structured interviews with eight employees working in local government organizations in East Java. The findings indicate that procedural compliance, hierarchical communication, peer norms, and legitimacy considerations influence employees' interpretation of fraud-related concerns and evaluation of whether reporting represents an appropriate administrative action. This adds a more contextual and process-based understanding to studies that often focus solely on personal factors. The study highlights that employees frequently engage in informal sensemaking with colleagues before considering formal disclosure. This extends the existing work by showing how silence or action is collectively produced through shared interpretations. Moreover, layered procedures and distributed responsibilities shape perceptions of oversight within the organization. Thus, this study contributes to the literature by demonstrating how institutional environments structure whistle-blowing behavior in bureaucratic organizations. Practically, the findings highlight the importance of leadership signals and organizational culture in strengthening the responsible voice regarding fraud risk.